2017
DOI: 10.1097/gme.0000000000000844
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in health-related quality of life, cardio-metabolic health, and fitness in postmenopausal women after a supervised, multicomponent, adapted exercise program in a suited health promotion intervention: a multigroup study

Abstract: Our findings parallel previous empirical evidence showing the benefits associated with regular exercise, and add evidence to the association of positive outcomes in HRQoL with improvements in cardio-metabolic health and fitness status after the adoption of an active lifestyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…En este estudio, la flexión de pierna, la flexión de brazo, la flexibilidad de tronco y la CF general estuvieron correlacionados con la mayoría de las dimensiones de CV de forma positiva y significativa. Estos resultados coinciden con estudios previos donde la CF del tren inferior y superior mostró asociación con la CV en las mujeres de mediana edad (Godoy-Izquierdo et al, 2017;Moratalla-Cecilia et al, 2016;Ruiz-Montero et al, 2021). Con respecto a la fuerza muscular, tanto la del tren superior como del tren interior podrían estar fuertemente relacionadas con menores síntomas menopaúsicos (Aparicio et al, 2017;Mishra, Devanshi, & Mishra, 2011).…”
Section: Discussionunclassified
“…En este estudio, la flexión de pierna, la flexión de brazo, la flexibilidad de tronco y la CF general estuvieron correlacionados con la mayoría de las dimensiones de CV de forma positiva y significativa. Estos resultados coinciden con estudios previos donde la CF del tren inferior y superior mostró asociación con la CV en las mujeres de mediana edad (Godoy-Izquierdo et al, 2017;Moratalla-Cecilia et al, 2016;Ruiz-Montero et al, 2021). Con respecto a la fuerza muscular, tanto la del tren superior como del tren interior podrían estar fuertemente relacionadas con menores síntomas menopaúsicos (Aparicio et al, 2017;Mishra, Devanshi, & Mishra, 2011).…”
Section: Discussionunclassified
“…The latter consist of both structural (e.g., objective BMI and body composition using bioelectrical impedance analysis) and functional indicators (e.g., heart functioning, aerobic aptitude index) as well as fitness indicators [ 92 ]. These measures are fully described elsewhere [ 93 , 94 ].…”
Section: Methodsmentioning
confidence: 99%
“…All included studies used surveys as their primary method of collecting data on psychological and social health outcomes, and most studies also reported menopausal stage and PA levels through self-reported questionnaires. The 33 intervention studies involved aerobic exercise [44][45][46][47][48][49][50], aerobic exercise and resistance training [38,[51][52][53][54], aerobic exercise vs yoga [39], resistance training [55,56], aerobic exercise and educational lectures [57][58][59][60][61][62], walking [63][64][65][66][67][68][69], walking vs yoga [70][71][72][73] and walking and educational lectures [74]. Twenty-one of the intervention studies reported using randomized controlled trials.…”
Section: Literature Searchmentioning
confidence: 99%
“…Finally, no significant association is found between PA levels and QoL in rural women [93]. Likewise, most intervention studies find that a variety of forms of PA have a positive impact on QoL, specifically aerobic exercise [38,44,51,54,57,66,99], resistance exercise [51,55], walking [57,70,72], and nutrition/health education combined with aerobic exercise [57,58]. In addition, one intervention study shows maintained improvements in QoL over time [54].…”
Section: Quality Of Lifementioning
confidence: 99%